The usage of AR in Malaysian school curriculum - Julaily Aida, Jusoh; Syarilla Iryani, A. Saany; Mohd Hafiz, Yusoff@Che Abdullah (2020)
In our modern times, smartphones have become an essential pillar of life, with which the holder can benefit in many important vital matters, and not just make and receive calls, and amuse his time with some applications. Therefore, instead of throwing and receiving calls and text messages and spending time in games, why not download these three useful applications, which will definitely help you in the educational aspect, whatever your studies. And applications are intended for smartphones running on any operating system. Type of hand instrument using Augmented Reality (AR) become produced for understudy from 1 to analyse Kemahiran Hidup difficulty and gaining knowledge of all the more correctly in college. Existing gaining knowledge of techniques are modified by AR advances and making use of mobile phones. This application would possibly have the choice to assist understudy from 1 to benefit proficiency with the kind of hand instrument an increasing number of wise and fun. A diffusion, this application will make use of shrewd 3D articles, sound and show records with the aim that understudies are keen on utilising this software. ADDIE approach is separated into 5 principle segments, especially the begin of the research levels, plan degrees, advancement ranges, execution levels and evaluation ranges. The usage of the Addie approach ensures that the development of the framework runs without problems and as indicated by means of arranging. The ordinary final results following the advancement of the proposed undertaking are the easy to apply interface. Multiplied truth with excellent interface on this utility so as to be blanketed to apply by using customer. Apart from that, powerful final results in getting facts in utilizing this transportable utility.